THE CONCEPT OF CREATIVE ECONOMY (International conference on multidisciplinary science, 2023)
The concept of the creative economy has gained prominence in recent years as a framework for understanding the intersection of culture, creativity, and economic development. This article explores the key elements and principles of the creative economy, highlighting its significance in today's globalized and digitized world. It discusses the role of creative industries, intellectual property, innovation, and the cultural and economic implications of fostering a creative economy. Furthermore, it examines the challenges and opportunities associated with this emerging paradigm.